A fibrin-supported myocardial organ culture for isolation of cardiac stem cells via the recapitulation of cardiac homeostasis. (April 2015) - Kim, Jong-Tae; Chung, Hye Jin; Seo, Ji-Yeon; Yang, Young-Il; Choi, Min-Young; Kim, Hyeong-In; Yang, Tae-Hyun; Lee, Won-Jin; Youn, Young Chul; Kim, Hye Jung; Kim, Yeon Mee; Lee, Hyukjin; et al.
Abstract: There is great interest in the development of cardiac stem cells (CSCs) cell-based therapeutics; thus, clinical translation requires an efficient method for attaining therapeutic quantities of these cells. Furthermore, an in vitro model to investigate the mechanisms regulating the cardiac homeostasis is crucial. We sought to develop a simple myocardial culture method for enabling both the recapitulation of myocardial homeostasis and the simultaneous isolation of CSCs. The intact myocardial fragments were encapsulated 3-dimensionally into the fibrin and cultured under dynamic conditions. The fibrin provided secure physical support and substratum to the myocardium, which mediated integrin-mediated cell signaling that allowed in situ renewal, outgrowth and cardiomyogenic differentiation of CSCs, mimicking myocardial homeostasis. Since our culture maintained the myocardial CSCs niches, it was possible to define the identity of in vitro renewed CSCs that situated in the interstitium between cardiomyocytes and microvessels. Lastly, the use of matrix-restricted fibrinolysis enabled the selective isolation of outgrown CSCs that retained the clonogenicity, long-term growth competency and cardiovascular commitment potential. Collectively, this myocardial culture might be used as an alternative tool for studying cardiac biology and developing cell-based therapeutics.